2016
DOI: 10.3892/ijo.2016.3713
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of AUF1 is involved in the proliferation of esophageal squamous cell carcinoma through GCH1

Abstract: Esophageal squamous cell carcinoma (ESCC) has one of the highest mortality rates worldwide. AU-rich element RNA-binding factor 1 (AUF1) is an established RNA-binding protein. AUF1 influences the process of development, apoptosis and tumorigenesis via interacting with adenylate-uridylate rich elements (AREs) bearing mRNAs. However, the clinical relevance of AUF1 and its biological function in ESCC progression have not been reported. In the present study, we first investigated the expression of AUF1 in the ESCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 31 publications
(37 reference statements)
3
36
0
Order By: Relevance
“…This RNA-binding protein regulates the expression of a rich array of proteins, many of which are the key players in cell cycle, apoptosis, and inflammation [ 42 , 43 ]. Studies have demonstrated that AUF1 shows both pro- and anti-apoptotic activity [ 35 , 44 , 45 ]. In this study, although we did not observe increased ratio of cells in the early phase of apoptosis when the expression of AUF1 was knocked down by specific siRNA, the proportion of cells in late apoptosis and necrosis was indeed elevated, indicating that AUF1 might play a role in the survival of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…This RNA-binding protein regulates the expression of a rich array of proteins, many of which are the key players in cell cycle, apoptosis, and inflammation [ 42 , 43 ]. Studies have demonstrated that AUF1 shows both pro- and anti-apoptotic activity [ 35 , 44 , 45 ]. In this study, although we did not observe increased ratio of cells in the early phase of apoptosis when the expression of AUF1 was knocked down by specific siRNA, the proportion of cells in late apoptosis and necrosis was indeed elevated, indicating that AUF1 might play a role in the survival of HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The hnRNP D, that is overexpression in Eca-109 esophageal cancer cell line, has been recognized to bind the 3 -UTR AUrich motifs of GTP cyclohydrolase (GCH1) transcripts causing GCH1 overexpression and enhanced cell proliferation and colony formation (Gao et al, 2016). Moreover, the hnRNP D protein can specifically bind to single-stranded d(TTAGGG)n human telomeric repeats through its C-terminal binding domain (BD2), thus impeding the formation of a DNA-quadruplex while favoring telomeres elongation and maintenance (Enokizono et al, 2005).…”
Section: Oncogenic Functions Of Hnrnps and Srsfsmentioning
confidence: 99%
“… CCH1 , which is a voltage-gated high-affinity calcium channel with several homologs that were UES, including: CACNA1A , underexpressed in breast, colorectal, esophageal, gastric, and brain cancers; CACNA1B , underexpressed in breast and brain cancers; CACNA1C , underexpressed in brain, bladder, lung, lymphoma, prostate, and renal cancers; CACNA1E , underexpressed in breast, brain, gastric, leukemia, lung, and prostate cancers; and CACNA1F , underexpressed in lymphoma [274] ; IZH1 , a yeast membrane protein involved in zinc ion homeostasis, having a human homolog, PAQR1/ADIPOR1 that encodes the adiponectin receptor protein 1, which is differentially regulated in breast cancers [278,279] ; FAT1 , a yeast fatty acid transporter and very long-chain fatty acyl-CoA synthetase that corresponds to SLC27A2 (very long-chain acyl Co-A synthetase), which is underexpressed in lung cancer [275], and SLC27A3 (long-chain fatty acid transport), which is hypermethylated in melanoma [276]; FOL2/GCH1 , a GTP-cyclohydrolase that catalyzes the first step in folic acid biosynthesis. Downregulation of GCH1 occurs in esophageal squamous cell carcinoma [277]. …”
Section: Resultsmentioning
confidence: 99%
“…FOL2/GCH1 , a GTP-cyclohydrolase that catalyzes the first step in folic acid biosynthesis. Downregulation of GCH1 occurs in esophageal squamous cell carcinoma [277].…”
Section: Resultsmentioning
confidence: 99%